2016
DOI: 10.1039/c5py01844g
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and tissue adhesiveness of temperature-sensitive hyperbranched poly(amino acid)s with functional side groups

Abstract: The adhesive strength of poly(amino acid)s can be improved by clicking a cross-link, forming a disulfide bond and so on. In addition, the adhesion strength becomes better on grafting with different monomers at 37 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…Thes uccess of synthetic adhesives in wet environments is most often conditioned by ap revious cleaning of the substrates,e ither by chemical treatments and/or partial drying. [101] An interesting alternative to avoid this preliminary step is the introduction of surface conditioners within the polymeric backbone to improve the close contact with the surface.T he objective is to minimise the effect of detrimental agents such as certain solvents or salts.F or example,s everal studies have demonstrated that the presence of cationic groups (such as iminium, ammonium, or guanidinium groups) in the material backbone significantly enhances its underwater adhesion (Figure 9), [101,[111][112][113][114][115][116][117] which is primarily the result of displacement of the surface salt from the substrate because of competition with the cationic groups included in the polymer backbone.T he flexibility and length of the cationic and the catecholic groups as well as the distance between them are crucial for enhancement of the adhesion. [113,115] Finding the optimum charge is challenging,asanexcess can be detrimental because of 1) the prevalence of charge-charge repulsions or 2) competition between cationic and catechol moieties for negative surfaces.…”
Section: Roles Of Other Functional Groups In the Polymeric Backbonementioning
confidence: 99%
“…Thes uccess of synthetic adhesives in wet environments is most often conditioned by ap revious cleaning of the substrates,e ither by chemical treatments and/or partial drying. [101] An interesting alternative to avoid this preliminary step is the introduction of surface conditioners within the polymeric backbone to improve the close contact with the surface.T he objective is to minimise the effect of detrimental agents such as certain solvents or salts.F or example,s everal studies have demonstrated that the presence of cationic groups (such as iminium, ammonium, or guanidinium groups) in the material backbone significantly enhances its underwater adhesion (Figure 9), [101,[111][112][113][114][115][116][117] which is primarily the result of displacement of the surface salt from the substrate because of competition with the cationic groups included in the polymer backbone.T he flexibility and length of the cationic and the catecholic groups as well as the distance between them are crucial for enhancement of the adhesion. [113,115] Finding the optimum charge is challenging,asanexcess can be detrimental because of 1) the prevalence of charge-charge repulsions or 2) competition between cationic and catechol moieties for negative surfaces.…”
Section: Roles Of Other Functional Groups In the Polymeric Backbonementioning
confidence: 99%
“…These were then soaked for 12 h in a PBS buffer solution (pH = 7.4) [36]. For the adhesion test, polyaspartamide glues were spread on two pieces (2.0 cm×1.5 cm cross area) of the porcine skin surface.…”
Section: Porcine Skin Preparation and Testmentioning
confidence: 99%
“…Porcine skin samples were cut into rectangular pieces (7.5 cm in length × 2.0 cm in width) and washed with a sodium chloride aqueous solution. These were then soaked for 12 h in a phosphate‐buffered saline (PBS) solution (pH = 7.4) . For the adhesion tests, polyaspartamide glues were spread on two pieces (2.0 cm × 1.5 cm) of the porcine skin surface.…”
Section: Methodsmentioning
confidence: 99%
“…For bioadhesive materials and applications, nontoxicity is as important as high adhesion performance. Nowadays, a wealth of reports has been published on a variety of potential bioadhesives using porcine skin as the substrate due to its similarity to the human dermis . Fan et al .…”
Section: Introductionmentioning
confidence: 99%